Determining Dust Sources of Middle East and Assessing Their Impact on Agricultural Lands in Euphrates-Tigris River Basin (Syria-Iraq) - Ayhan Ateşoğlu; Metin Tunay; Talha Berk Arıkan; Saffet Yıldız (Doğal Afetler ve Çevre Dergisi, 2018)
This study was carried out in order to determine the dust sources in the Middle status of Middle East region between 2000-2015years have been analyzed using Collect earth methodology initiated by United Nations Food AND Agriculture Organized (FAO) in Antalya/Turkey on July 2015 and the results were reported by FAO.As being free of charge and an open source tool, the Collect Earth software uses very high resolution multi-temporal images from Google Earth and Bing Maps. At the same time, it also allows users to utilize all the datasets generated from mid-resolution images of Modis, Landsat 5, 7 and 8. Data analysis and numerical results can be achieved through SAIKU a statistical analysis program. In this study, by using GIS techniques on the dataset generated for the entire Middle East region, a map of risk level classes for dust resources areas were created. According to the risk classes map, it was confirmed that 63.6% of the total area of Iraq, and 53.7% of the total area of Syria were in the third-degree dust resources area. In addition, when the distribution of water resource areas consider highly important for Middle East region are examined according to risk level classes, it is seen that the largest water resources areas of Iraq were in the third-degree dust resources region with 71.3% while for Syria the largest water resource area were in the fourth and fifth degree dust resources region with 27.4% and 25.9%, respectively. By interpreting the results of the classification with regard to the Middle East, especially respect to sand/dune areas, agricultural lands and water resources, the evaluations are made especially on the scale of Iraq and Syria affected by Euphrates and Tigris River.